Single or Combined Valve Surgery and Concomitant Right Coronary Artery Bypass through Right Anterior Minithoracotomy Approach - Hasde, Ali Ihsan; Sarıcaoğlu, Mehmet Cahit; Kılıçkap, Mustafa; Durdu, Mustafa Serkan (The Thoracic and Cardiovascular Surgeon, 2022)
Background Patients with combined valve and coronary artery disease are commonly performed by standard median sternotomy approach for coronary artery bypass grafting (CABG) and valve surgery. The purpose of this study is to describe our experience and show feasibility and safety of minimally invasive approach to single or combined valve pathology with single-vessel right coronary artery (RCA) disease, even if it is suitable to percutaneous coronary intervention.Methods This retrospective study comprised 28 consecutive patients who underwent single or combined valve surgery concomitant right CABG through right anterior minithoracotomy between February 2018 and December 2020. Preoperative evaluation, intraoperative, and postoperative outcomes were reviewed and analyzed.Results There were 12 men and 16 women. The mean age was 71.46 ± 6.82 years. Ten patients were in New York Heart Association class III or IV. The mean cardiopulmonary bypass and aortic cross-clamping times were 117.6 ± 21.3 and 98.1 ± 22.6 minutes, respectively. The mean time to extubation was 9.7 ± 5.6 hours, the mean intensive care unit stay was 37.4 ± 14.6 hours, and the mean hospital stay was 6.9 ± 3.2 days. There was one patient who underwent reoperation for bleeding. There were no instances of postoperative stroke, myocardial infarction, renal failure, or wound infection. The mean follow-up was 19 ± 2.4 months.Conclusion Presence of RCA lesion is not a contraindication for minimally invasive approach in cases who underwent single or combined valve surgery. Combined valve surgery and right CABG via right anterior minithoracotomy are a safe and feasible option to standard median sternotomy surgery, even if RCA lesions seem suitable for stenting.
Keywords: minimally invasive surgery; valve surgery; CABG